MNK-eIF4E signalling is a highly conserved mechanism for sensory neuron axonal plasticity: evidence from Aplysia californica. (11th November 2019) - Mihail, Sandra M.; Wangzhou, Andi; Kunjilwar, Kumud K.; Moy, Jamie K.; Dussor, Gregory; Walters, Edgar T.; Price, Theodore J.
Abstract : Injury to sensory neurons causes an increase in the excitability of these cells leading to enhanced action potential generation and a lowering of spike threshold. This type of sensory neuron plasticity occurs across vertebrate and invertebrate species and has been linked to the development of both acute and persistent pain. Injury-induced plasticity in sensory neurons relies on localized changes in gene expression that occur at the level of mRNA translation. Many different translation regulation signalling events have been defined and these signalling events are thought to selectively target subsets of mRNAs. Recent evidence from mice suggests that the key signalling event for nociceptor plasticity is mitogen-activated protein kinase-interacting kinase (MNK) -mediated phosphorylation of eukaryotic translation initiation factor (eIF) 4E. To test the degree to which this is conserved in other species, we used a previously described sensory neuron plasticity model in Aplysia californica . We find, using a variety of pharmacological tools, that MNK signalling is crucial for axonal hyperexcitability in sensory neurons from Aplysia . We propose that MNK-eIF4E signalling is a core, evolutionarily conserved, signalling module that controls nociceptor plasticity. This finding has important implications for the therapeutic potential of this target, and it provides interesting clues about the evolutionary origins of mechanisms important for pain-related plasticity. This article is part of the Theo Murphy meeting issue 'Evolution of mechanisms and behaviour important for pain'.